2011
DOI: 10.1111/j.1365-2966.2011.18850.x
|View full text |Cite
|
Sign up to set email alerts
|

HD 97394: a magnetic Ap star with high cerium overabundance★

Abstract: We report a spectroscopic analysis of the chemically peculiar Ap star HD 97394. The stellar spectrum is rich in lines of rare earth elements with large overabundances, especially cerium, gadolinium and europium. Enhancement of the abundances of these rare earths shows this star to be one of the most peculiar stars. Very large overabundances were found for lines of Ce iii and Eu iii. Abundances obtained from second ionization lines of Nd, Ce and Eu are about 2 dex higher than for those of the first ionization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Together with previous papers (Freyhammer et al 2008; Elkin et al 2010a; Elkin, Kurtz & Mathys 2011), we have found a total of 34 new magnetic stars with resolved and partly resolved Zeeman components using high‐resolution spectra from our FEROS survey of cool Ap stars. Among them, we found several stars with a mean magnetic field modulus more than 10 kG.…”
Section: Discussionsupporting
confidence: 69%
“…Together with previous papers (Freyhammer et al 2008; Elkin et al 2010a; Elkin, Kurtz & Mathys 2011), we have found a total of 34 new magnetic stars with resolved and partly resolved Zeeman components using high‐resolution spectra from our FEROS survey of cool Ap stars. Among them, we found several stars with a mean magnetic field modulus more than 10 kG.…”
Section: Discussionsupporting
confidence: 69%
“…As the table shows, there is a significant over-abundance of the rare earth elements in HD 24355 when compared to the solar values, with some elements still enhanced when compared to other roAp stars (e.g. Bruntt et al 2008;Elkin, Kurtz & Mathys 2011;Smalley et al 2015).…”
Section: Identification Of Rare Earth Elementsmentioning
confidence: 93%
“…Martinez, Kurtz & Kauffmann 1991;Martinez & Kurtz 1994), with later studies using high-resolution spectroscopy to detect line profile variations in Ap stars caused by pulsational velocity shifts (e.g. Savanov, Malanushenko & Ryabchikova 1999;Kochukhov & Ryabchikova 2001;Hatzes & Mkrtichian 2004;Mkrtichian et al 2008;Elkin et al 2010;Elkin, Kurtz & Mathys 2011;Kochukhov et al 2013). Most recently, the use of the Super-WASP (Wide Angle Search for Planets) ground-based photometric survey led to the identification of 11 roAp stars (Holdsworth et al 2014a;Holdsworth 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The use of oscillator strengths compiled in the DREAM database also allowed to identify new lanthanide lines in many different high-resolution astrophysical spectra and to deduce reliable abundances of rare earth elements (sometimes up to several orders of magnitude higher than the solar values in the case of various chemically peculiar stars), see, e.g., [45][46][47][48][49][50][51][52][53][54][55][56]. To give just one noteworthy specific example, we will mention the recent multicolour photometric investigation of the eclipsing binary system HD 66051 [53] carried out using, among other data, the spectroscopic parameters of the second and third spectra of lanthanides taken from the DREAM database.…”
Section: Some Examples Of Uses Of Atomic Data From Dreammentioning
confidence: 99%